’Genus X2’ finally named: discovery of males of Clavomicrus gen. n. in the Philippines (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2019)
In 2011 phylogenetic relationships of ’Cephennomicrus group’ of Cephenniini were studied and several new genera were described. Two taxa, each represented by a single female and referred to as genus X1 (Sulawesi) and X2 (Philippines), were included in that study. Recently, a new sample of scydmaenines from Luzon has become available to my study, including a series of male and female specimens of the genus X2. Clavomicrus orousseti gen. & sp. n. is here described based on this material. SEM data are added to morphological structures previously illustrated on the basis of transparent slide preparations. Clavomicrus is the second genus of Cephenniini with the antennomere X and XI fused together into a histerid-like, abruptly delimited, oval club.